Ciprofloxacin population pharmacokinetics during long-term treatment of osteoarticular infections. (7th August 2021) - Zahr, Noël; Urien, Saik; Aubry, Alexandra; Chauvin, Charlotte; Comets, Emmanuelle; Llopis, Benoit; Tissot, Nadine; Noe, Gaëlle; Fourniols, Eric; Jaureguiberry, Stéphane; Bleibtreu, Alexandre; Funck-Brentano, Christian; et al.
Abstract: Background: Ciprofloxacin is an antibiotic used in osteoarticular infections owing to its very good bone penetration. Very few pharmacokinetic data are available in this population. Objectives: To investigate oral ciprofloxacin population pharmacokinetics in adult patients treated for osteoarticular infections and propose guidance for more effective dosing. Methods: A retrospective population-pharmacokinetic analysis was performed on 92 consecutive hospitalized patients in the orthopaedic department. Ciprofloxacin plasma samples were obtained on one or two occasions during treatment. Plasma concentration was measured using ultra-performance liquid chromatography system coupled with tandem mass spectrometry. Data analysis was performed using a non-linear mixed-effect approach via Monolix 2019R2. Results: A total of 397 plasma samples were obtained with 11.5% and 41.6% of patients being below the therapeutic target for Gram-negative and staphylococcal infections, respectively. Ciprofloxacin pharmacokinetics were best described by a two-compartment model with a first-order absorption. Ciprofloxacin apparent plasma clearances and volumes of distribution were dependent on patients' fat-free mass according to the allometric rule. Elimination clearance was also positively related to renal function through the modification of diet in renal disease equation (MDRD) and rifampicin co-administration. When patients are co-treated with rifampicin, ciprofloxacin dosage should be increased by 50% to 60%. Conclusions: This study showed that free-fat mass was a better size predictor than total body weight for ciprofloxacin clearance and volumes terms. Moreover, both MDRD and rifampicin status were significant predictors of individual ciprofloxacin clearance. Our study suggests that individual adjustment of ciprofloxacin dose in osteoarticular infections with less-susceptible bacteria might be indicated to reach required efficacy targets.